Comity and Jurisdictional Restraint in Vanuatu - Mortensen, Reid (Victoria University of Wellington Law Review, 2002)
This article revisits Pacific Courts' treatment of two procedural tools for locating litigation in the best court: the doctrine of forum non conveniens and the anti-suit injunction. The recent reporting of the Vanuatu Court of Appeal's decision in Chan Wing (Vanuatu) Limited v Motis Pacific Lawyers shows that the court accepted orthodox principles for both procedures, representing an improvement in adjudication on the conduct of international litigation in the Pacific. Chan Wing also reveals a technique by which courts exercising the jurisdiction to grant anti-suit injunctions can unilaterally improve the enforceability of their own judgments in other countries. It is suggested that respect for international comity in Pacific Island adjudication has reached new heights in the principles stated in Chan Wing for the plea of forum non conveniens and the grant of anti-suit injunctions. However, it also seems that the Court of Appeal's efforts at enhancing the extraterritorial enforcement of its own judgments offends settled principles governing friendly and courteous relations between courts.